Islamic Philanthropy and Positive Law Regulation: A Social Jurisprudence Study of the South Sulawesi Dompet Dhuafa Fund Donation Program - Wildan, Muhammad; Asni, Asni; Sanusi, Nur Taufiq (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
The main objective of this study is to determine the Perspective of Social Jurisprudence and Positive Law on Social Fund Donations by Philanthropic Institutions (Dompet Dhuafa South Sulawesi). The objectives of the sub-problems are: 1) To determine the Mechanism of the Dompet Dhuafa Philanthropic Institution of South Sulawesi on Social Fund Donations. 2) To determine the Perspective of Social Jurisprudence on the Deduction of Social Fund Donations by Philanthropic Institutions (Dompet Dhuafa). 3) To determine the Perspective of Positive Law on the Deduction of Social Fund Donations by Philanthropic Institutions (Dompet Dhuafa). This study uses qualitative research with the type of field research, which is carried out by collecting primary data through observation, interviews and documentation. In addition, the data is also strengthened by tracing laws, books, journals, and visiting the websites of philanthropic institutions related to the topic of study discussed. Then, data processing and analysis techniques are carried out by data reduction, data presentation, and drawing conclusions. The results of the study show that: 1) LAZ Dompet Dhuafa South Sulawesi collects funds from ZISWAF and CSR, with 12.5% ​​for operational costs and amil rights. Funds are distributed to health, education, economic, social and da’wah programs. 2) Zakat deductions are regulated in QS. At-Taubah/9: 60 and MUI Fatwa No. 8/2011, with 12.5% ​​ownership rights and the views of KH. Sahal and KH. Ali Yafie emphasized the importance of social contributions through zakat institutions to empower society according to the principles of maqāṣid al-syarīʿah. 3) Positive law in Indonesia towards Islamic philanthropic institutions is regulated in Article 67 Paragraph 2 in PP No. 4/2014 concerning Implementation of Law no. 23/2011 concerning Zakat Management, as well as KEMENAG Decree No. 733/2018 and BAZNAS rule no. 1/2016 which regulates social funding cuts of up to 20% outside of zakat funds. In contrast to the regulations for general philanthropic institutions or Money and Goods Collection (PUB) institutions regulated in Article 6 paragraph (1) of the Republic of Indonesia Government Regulation No. 29/1980 concerning the implementation of donation collection, namely the financing of donation collection efforts of a maximum of 10% of the results of the relevant donation collection. And PERMENSOS No. 8/2021 concerning the Implementation of Money or Goods Collection, and there are no regulations yet governing the operational salaries of administrators of general philanthropic institutions.